The regulation of ISG20 expression on SARS-CoV-2 infection in cancer patients and healthy individuals - Cheng, Jingliang; Fu, Jiewen; Tan, Qi; Liu, Zhiying; Guo, Kan; Zhang, Lianmei; He, Jiayue; Zhou, Baixu; Liu, Xiaoyan; Li, Dabing; Fu, Junjiang (Frontiers in Immunology, 2022)
ISG20 inhibits viruses such as SARS-CoV-2 invasion; however, details of its expression and regulation with viral susceptibility remain to be elucidated. The present study analyzed ISG20 expression, isoform information, survival rate, methylation patterns, immune cell infiltration, and COVID-19 outcomes in healthy and cancerous individuals. Cordycepin (CD) and N6, N6-dimethyladenosine (m62A) were used to treat cancer cells for ISG20 expression. We revealed that ISG20 mRNA expression was primarily located in the bone marrow and lymphoid tissues. Interestingly, its expression was significantly increased in 11 different types of cancer, indicating that cancer patients may be less vulnerable to SARS-CoV-2 infection. Among them, higher expression of ISG20 was associated with a long OS in CESC and SKCM, suggesting that ISG20 may be a good marker for both viral prevention and cancer progress. ISG20 promoter methylation was significantly lower in BLCA, READ, and THCA tumor tissues than in the matched normal tissues, while higher in BRCA, LUSC, KIRC, and PAAD. Hypermethylation of ISG20 in KIRC and PAAD tumor tissues was correlated with higher expression of ISG20, suggesting that methylation of ISG20 may not underlie its overexpression. Furthermore, ISG20 expression was significantly correlated with immune infiltration levels, including immune lymphocytes, chemokine, receptors, immunoinhibitors, immunostimulators, and MHC molecules in pan-cancer. STAD exhibited the highest degree of ISG20 mutations; the median progression-free survival time in months for the unaltered group was 61.84, while it was 81.01 in the mutant group. Isoforms ISG20-001 and ISG20−009 showed the same RNase_T domain structure, demonstrating the functional roles in tumorigenesis and SARS-CoV-2 invasion inhibition in cancer patients. Moreover, CD and m62A increase ISG20 expression in various cancer cell lines, implying the antiviral/anti-SARS-CoV-2 therapeutic potential. Altogether, this study highlighted the value of combating cancer by targeting ISG20 during the COVID-19 pandemic, and small molecules extracted from traditional Chinese medicines, such as CD, may have potential as anti-SARS-CoV-2 and anticancer agents by promoting ISG20 expression.